Inconsistency, Paradox and Linguistic Content. Did Bhartṛhari offer a solution for Truth-Paradoxes? - Oetke, Claus (2014)
The article attempts to clarify the nature of truth-paradoxes by demonstrating why it cannot be maintained that a particular philosophical treatise offers a way to their solution. In the light of objective qualities of statements leading to paradoxes of truth it emerges that the question of the nature of the content to which properties of (absolute) truth can be ascribed possesses critical relevance. This supports the dismissal of a claim made by some scholars with respect to the pertinent text.